SANITARY EFFLUENT POST-TREATMENT SYSTEM BY OVERLAND FLOW METHOD FOR PATHOGENS REMOVAL - MAGALHÃES, VERÔNICA C.; PIRES, MARTA S. G.; CORAUCCI FILHO, BRUNO; STEFANUTTI, RONALDO; KAWAZOE, URARA (Revista Brasileira de Engenharia de Biossistemas, 2009)
Natural removal of protozoa and helminths from an anaerobic pond (lagoon) was evaluated using theeffluent post-treatment system by overland flow process. The method was carried out in the SewageTreatment Station of Graminha, in the city of Limeira, State of São Paulo, Brazil. The effluent wasreleased onto a 45 meter-long and 4.2 meter-wide slope with an inclination of 3.5%, covered withTifton 85 (Cynodon sp.) grass. The rate of flow used was 0,20 m3/h and water samples were collectedin five different points every 15 daysduring a period of ten months. The point 01 was located at thebeginning of the effluent release and each subsequent collection point was at every 10 meters alongthe slope. The highest concentrations of pathogens were detected in the first 10 meters of the slope.The process was able to remove most of the pathogens, which suggests that reuse of domesticeffluents treated in this manner is suitable for activities such as irrigation